X-ray powder diffraction data for eluxadoline nitrate monohydrate, C32H35N5O5⋅2HNO3⋅H2O. Issue 3 (September 2020) - Wei, Xin; Suo, Zi Li; Zhang, Man; Tang, Pei Xiao; Li, Hui
Abstract : Single-crystal and powder X-ray diffraction data, collected at room temperature, unit-cell parameters and space group for eluxadoline nitrate monohydrate, C32 H35 N5 O5 ⋅2HNO3 ⋅H2 O, are reported [ a = 11.066(5) Å, b = 13.452(6) Å, c = 24.373(9) Å, unit-cell volume V = 3628.15 Å 3, Z = 4, ρ cal = 1.344 g⋅cm −3, and space group P 21 21 21 ]. All the diffraction peaks in the experimental pattern have been indexed and are consistent with the P 21 21 21 space group.